Finite-Time Synchronization Between Two Different Chaotic Systems by Adaptive Sliding Mode Control - Tino, Nipaporn; Niamsup, Piyapong (Frontiers in Applied Mathematics and Statistics, 2021)
The finite-time chaos synchronization between two different chaotic systems with uncertain parameters and external disturbances is studied. A new and improved adaptive fast nonsingular terminal sliding mode control (ANFTSM) has been designed for a fast rate convergence of tracking error to zero in finite time. The effectiveness of the proposed control method is shown in simulation results.